Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Pada Perusahaan Pertambangan Yang Terdaftar di BEI Periode 2019-2022 - Musari, Ila; Azis, Muhammad; Hasyim, Sitti Hajerah (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze the influence of Good Corporate Governance (Board of Commissioners and audit committee) on financial performance in mining companies listed on the IDX. The research variables are: (1) Financial Performance as the dependent variable (Y) measured by Return on Assets (ROA) at the end of each period, (2) Good Corporate Governance (X). By using the purposive sampling technique, 8 companies were obtained that met the criteria. The data were then analyzed using Linear Regression test. The results of the study show that there is a positive relationship between the variable Good Corporate Governance (Board of Commissioners) with Financial Performance, but there is no positive relationship between the variable Good Corporate Governance (Audit Committee) with Financial Performance.